2016
DOI: 10.18520/cs/v110/i10/1929-1938
|View full text |Cite
|
Sign up to set email alerts
|

Impact Ejecta Characterization for Small-Sized Fresh and Degraded Lunar Craters Using Radar Data

Abstract: Ejecta distribution studies for large-sized (>10 km) lunar craters have been carried out earlier, but similar studies on smaller craters are lacking mainly due to data resolution limitations. Here we present a detailed quantification on spatial deposition of ejecta for small-sized lunar craters (<6 km). Using data from Mini RF instrument on-board NASA's Lunar Reconnaissance Orbiter, four Stokes parameters that differentiate and describe the observed backscattered electromagnetic field are calculated. We use th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The difference between the Clementine results and CELMS results is probably from contamination of the impact ejecta from other regions, which plays an important role in the measured optical data (Lucey et al 1998;Wu et al 2012). After all, Aristarchus, Copernicus and Kepler craters are located not far from the belt, and even the ejecta from Tycho crater at a far distance also altered the surface compositions to some extent (Desai et al 2014). Moreover, Adams et al (1978);Haruyama et al (2009) suggested that higher FTAs mostly appear in younger basalts.…”
Section: A New View About Mare Volcanismmentioning
confidence: 94%
“…The difference between the Clementine results and CELMS results is probably from contamination of the impact ejecta from other regions, which plays an important role in the measured optical data (Lucey et al 1998;Wu et al 2012). After all, Aristarchus, Copernicus and Kepler craters are located not far from the belt, and even the ejecta from Tycho crater at a far distance also altered the surface compositions to some extent (Desai et al 2014). Moreover, Adams et al (1978);Haruyama et al (2009) suggested that higher FTAs mostly appear in younger basalts.…”
Section: A New View About Mare Volcanismmentioning
confidence: 94%